"Diabetes and Metabolism Disorders Medicinal Plants: A Glance at the Past and a Look to the Future 2018": Antihyperglycemic Activity of Hamelia patens Jacq. Extracts. (27th August 2018) - Rugerio-Escalona, Catalina; Ordaz-Pichardo, Cynthia; Becerra-Martinez, Elvia; Cruz-López, María del Carmen; López-y-López, Victor E.; Mendieta-Moctezuma, Aarón; Maldonado-Mendoza, Ignacio E.; Jiménez-Montejo, Fabiola E.
Abstract : Diabetes is one the world's most widespread diseases, affecting over 327 million people and causing about 300, 000 deaths annually. Despite great advances in prevention and therapy, existing treatments for this disorder have serious side effects. Plants used in traditional medicine represent a valuable source in the search for new medicinal compounds. Hamelia patens Jacq. has been used for treating diabetes and, so far, no reports have been made on the in vivo antihyperglycemic activity of this plant. The present study on H. patens aimed to test the antihyperglycemic effect of repeated administrations of the crude and fractional methanolic extracts (CME and FME, respectively) on rats with hyperglycemia induced by streptozotocin. After 10 administrations (20 days), each extract had lowered blood glucose to a normal level. The extracts produced effects similar to metformin. Of the five compounds identified by chromatographic analysis of the extracts, epicatechin and chlorogenic acid demonstrated antihyperglycemic effect. The antioxidant activity of the extracts was evidenced by their IC50 values (51.7 and 50.7 μ g/mL, respectively). The LD50 ≥2000 mg/Kg suggests low toxicity for both CME and FME. Thus, considering that the antihyperglycemic and antioxidant effects of metformin and extracts from H. patens were comparable, the latter may be efficacious for treating diabetes.